Postural control of Parkour athletes compared to recreationally active subjects under different sensory manipulations: A pilot study - Jabnoun, S.; Borji, R.; Sahli, S. (European Journal of Sport Science, 2019)
In Parkour activity, the aim is to move from one place to another as quickly and efficiently as possible by running, climbing, swinging, vaulting, rolling, crawling and jumping on tiny obstacles?…?. Performing these actions places a great demand on the postural control system. The purpose of the present study was to investigate postural control of Parkour practitioners - called Traceurs - compared to recreationally active (RA) subjects in different postural conditions after manipulating the visual and/or proprioceptive sensory inputs. Ten Traceurs (mean experience 5.9 ± 0.9 years; >5 hours per week) and 10 RA subjects participated in this study. We measured the centre of pressure area (CoPA) of the upright standing bipedal and unipedal postures in different postural conditions: on a firm and on a foam surfaces; on an oscillating surface in the sagittal plane and in the frontal plane in eyes open and eyes closed. To evaluate vision contribution, the Romberg index (RI) was calculated. Results showed that Traceurs presented a significant (P < .001) lower CoPA values compared to RA subjects in eyes closed condition, suggesting that they were able to maintain a better balance control when vision is removed. Traceurs seems to be less dependent on visual cues (lower RI values) and proprioceptive inputs for maintaining balance than RA subjects. According to our study, Parkour training (experience for at least five years with a minimum of five hours per week) may improve postural abilities of young adult practitioners in specific postural conditions.